2014
DOI: 10.1089/jwh.2014.4766
|View full text |Cite
|
Sign up to set email alerts
|

Stuck in the Out-Group: Jennifer Can't Grow Up, Jane's Invisible, and Janet's Over the Hill

Abstract: Fifty years after Title IX, women remain sparsely represented in high ranks and leadership in academic medicine. Although men and women enter the career pipeline at similar rates, academic medicine does not equivalently advance them. Currently, women account for 32% of associate professors, 20% of full professors, 14% of department chairs, and 11% of deans at U.S. medical schools-far from the near sex parity seen in medical students since the 1990s. Over 30 years of research confirms that gender stereotypes ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 24 publications
(23 reference statements)
1
36
0
1
Order By: Relevance
“…Each received a packet that included several topic-relevant articles 18,4447 and an informational book on women’s philanthropy. 48 Presentations and small-group discussions focused on topics concerning endowed chairs in women’s health, including…”
Section: Testing the Premisementioning
confidence: 99%
“…Each received a packet that included several topic-relevant articles 18,4447 and an informational book on women’s philanthropy. 48 Presentations and small-group discussions focused on topics concerning endowed chairs in women’s health, including…”
Section: Testing the Premisementioning
confidence: 99%
“…Following an assessment of the effect of specialty and gender on teachers at a Swedish medical school, Risberg et al () concluded that to improve working climate and reduce segregation, there was a need to make efforts to increase gender awareness among medical professionals through educational programs where continuous reflections about gender attitudes were encouraged. Pfleiderer et al () also recommend “using meaningful examples on a regular basis—ideally in a longitudinal manner.” They believe that it is important that “The content of teaching should be selected by the lecturers and full professors and be considered within students' exams” but emphasize that for this to be successful, the “absolute support of the respective medical faculties as well as the integration of these gender‐specific learning objectives into the national competence‐based learning catalogue for medical education is obligatory.” Kaatz and Carne () argue that, although there is a critical need to address stereotype‐based gender bias for the future of academic medicine, policies alone will not achieve gender equity in the academic medicine workforce. They provide examples of “interventions that treat gender bias as a remediable habit” which they say “show promise in promoting gender equity and transforming institutional culture to achieve the full participation of women at all career stages.” What is important, they add, is “to recognize when gender stereotyped assumptions are influencing judgments and decision making in ourselves and others, [to] challenge them as unjust, and deliberately practice replacing them with accurate and objective data.” Wong () strongly advocates medical curricula change to address gender inequalities in health and gender bias in medicine.…”
Section: Recommendationsmentioning
confidence: 99%
“…Yet, fixing the numbers is easier said than done. Although female students outnumber male students in medical schools, women are still underrepresented at higher levels in the medical profession (17). Gendered processes of inclusion and exclusion still play a role in medical training and more so at the expense of female graduates (3).…”
Section: Fixing the Numbersmentioning
confidence: 99%